M.N. Boltayev’s Thoughts on “Hegel’s Absolute Idealism” Dedicated to Western Philosophy - Usmonjonovna, Asrorova (Buletin Antropologi Indonesia, 2025)
This article discusses the work «Absolute Idealism of Hegel” from among the works of the philosopher scientist M.N. Boltaev dedicated to Western philosophy. In this, the great ideological predecessors of Master Hegel, the life and works of Fichte, Fichtean idealism as a description of the «foundation” of Kantian criticism, as well as issues related to science education and Fichteian idealism are covered.